Preparation and Fractal Research of Activated Carbon from Sludge with ZnCl2/CuCl2 as Activating Agent - Zuo, Ning; Mu, De-Wei; Miao, Ji-Lun; Li, Xia; Tan, Xue-Mei (Asian Journal of Chemistry, 2014)
Activated carbon was prepared with sewage sludge as raw material and ZnCl2/CuCl2 as activating agent by low tempertaure carbonization method. The optimum preparation conditions were activation temperature 534 °C, activation time 60 min, ZnCl2 concentration 3 mol/L, CuCl2 concentration 0.3 mol/L, the iodine adsorportion value was 534 mg/g. The prepared sludge carbons have a large amount of micropores, also have mesopores and macropores, with a BET surface area at 784.89 m2/g and a Langmuir surface area at 1053.69 m2/g. Adsorption of pharmaceutical wastewater on sludge activated carbon was conducted. The data were fitted by Freundlich equation. The sludge activated carbon had fractal characteristics, the iodine adsorportion value grow with the fractal dimension and the roughness.